Developing Websites to Optimize Digital Marketing and Increase the Competitiveness of Small and Micro Agribusiness Enterprises - Zaky, Sultan; Relawati, Rahayu; Agustina, Yohana; Trushkina, Nataliia (HABITAT, 2026)
Purpose: This study purposes to evaluate the effectiveness of the website of PT. Kreasi Tani Bumiaji uses the AIDA (Attention, Interest, Desire, Action) model to achieve purchase intent and WebQual (usability, information quality, service interaction quality) model to measure website quality. Design/Methodology/Approach: Data were collected through observation, interviews, and documentation from November 15 to November 31, 2024, then analyzed using descriptive analysis methods and PLS-SEM. Findings: The results showed that the quality of the website was classified as good with a score of Usability (4.24), very good Quality of Information (4.28), and very good Quality of Service Interaction (4.21). The AIDA Attention dimension is very good (4.26), Interest is very good (4.15), and Desire is very good (4.23) is at a high level, but Good Action (4.13) still needs to be improved to encourage intent to buy. Structural analysis shows that Information Quality and Service Interaction Quality have a significant effect on Attention. Attention affects Interest, which affects Desire and ultimately Action, according to the AIDA model. Overall, the website is effective in attracting consumers attention and interest and providing a good user experience, but it needs to optimize features and interactivity to maximize purchase conversions and digital promotion results. Originality/Value/Novelty: the integration of Artificial Intelligence technology such as chatbots and recommendation systems increases interactivity and personalization of content, strengthening the digital competitiveness of PT. Kreasi Tani Bumiaji.